Developing a habitat suitability index to guide restoration of New England cottontail habitats - Alena Warren; John A. Litvaitis; Donald Keirstead (Wildlife Society Bulletin)
ABSTRACT Populations of taxa dependent on young forests and shrublands in the northeastern United States are declining in response to habitat loss and fragmentation. In particular, the reduction in distribution and abundance of the New England cottontail (Sylvilagus transitionalis; NECs) prompted consideration to list it as federally threatened or endangered. In response to those concerns, a range‐wide conservation strategy for NECs has been developed that includes managing >20,000 ha of thicket habitats. Although much is known about the habitat associations of NECs, there is no obvious approach for evaluating the suitability of sites managed for them. We developed a habitat suitability model that conservationists can use to monitor progress in generating and maintaining habitats for NECs. We relied on literature reviews, expert opinions, and field data to identify habitat features that can be measured and indexed and used in a simple model to rank patches of habitat on a scale of 0 (unsuitable) to 1 (high suitability). Important features included dense understory vegetation, summer forage, and the presence–absence of additional refuges (e.g., constructed brush piles). We used our model to rank 60 managed habitats and found general agreement with opinions of an expert panel. There are obvious advantages to using a habitat‐suitability model during efforts to restore populations of NECs: it provides a consistent approach for monitoring management actions, can be used to identify site‐specific limitations prior to releasing cottontails in vacant habitats, and can be used to track suitability over time and alert managers of potential habitat deficiencies. Our suitability model also can be modified to accommodate new information and changing conditions. © 2015 The Wildlife Society.